A Comparative Determination of the Physicochemical Properties of the Crude and Refined Products of Palm oil and Soybean oil - ESAN, Akintomiwa Olumide; OLAWORE, Ibidotun Theophilus; FAYOKUN, Grace Ibukunoluwa; ADEREMI, Samuel Adeyeoba; BADMUS, Deborah Adejoke; OLUSHOLA, Funmilayo Yetunde; URANTA, Samuel Sodienye (ABUAD Journal of Engineering and Applied Sciences, 2024)
This study compares the physicochemical properties of crude and refined palm oil and soybean oil. Key parameters such as acid value, peroxide value, saponification value, free fatty acid, and iodine value were analysed. Crude palm oil exhibited higher acid and saponification values, while refined oils showed improved stability and reduced free fatty acids. Refining reduced oxidation susceptibility in soybean oil but increased the peroxide value in palm oil. The results reveal significant changes in oil quality post-refinement, impacting nutritional and industrial applications. These findings highlight the critical role of refining in improving oil quality and safety for industrial applications. However, the effects of refining vary depending on the oil type.